2017
DOI: 10.1002/dvg.23028
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay or should I go? Cadherin function and regulation in the neural crest

Abstract: Our increasing comprehension of neural crest cell development has reciprocally advanced our understanding of cadherin expression, regulation, and function. As a transient population of multipotent stem cells that significantly contribute to the vertebrate body plan, neural crest cells undergo a variety of transformative processes and exhibit many cellular behaviors, including epithelial-to-mesenchymal-transition (EMT), motility, collective cell migration, and differentiation. Multiple studies have elucidated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 174 publications
(289 reference statements)
2
42
0
Order By: Relevance
“…Cell adhesion proteins have long been studied for their role in the process of NC EMT (reviewed in Barriga & Mayor, 2015; Strobl-Mazzulla & Bronner, 2012a; Taneyhill & Schiffmacher, 2017); however, recent analyses have determined that these proteins may also have additional roles in NC specification and induction. Recent evidence has determined that NC specifiers and EMT-inducing factors like SNAI2 have alternate early roles in cell fate specification.…”
Section: | Signaling Events Regulating Nc Inductionmentioning
confidence: 99%
“…Cell adhesion proteins have long been studied for their role in the process of NC EMT (reviewed in Barriga & Mayor, 2015; Strobl-Mazzulla & Bronner, 2012a; Taneyhill & Schiffmacher, 2017); however, recent analyses have determined that these proteins may also have additional roles in NC specification and induction. Recent evidence has determined that NC specifiers and EMT-inducing factors like SNAI2 have alternate early roles in cell fate specification.…”
Section: | Signaling Events Regulating Nc Inductionmentioning
confidence: 99%
“…Notably, this ADAM10‐dependent proteolytic event is triggered by BMP activity (Shoval et al, ) (Figure ). Subsequent studies confirmed and extended these findings implicating ADAM‐dependent proteolysis of N‐cadherin, cadherin 6B, and cadherin 11 in the onset of NC EMT at cranial levels of the axis (Alfandari et al, ; McCusker, Cousin, Neuner, & Alfandari, ; Monsonego‐Ornan et al, ; Schiffmacher et al, ) and reviewed in (Taneyhill & Schiffmacher, ).…”
Section: The Dynamics Of Nc Emt In the Trunkmentioning
confidence: 80%
“…Many cadherins have been implicated in NC EMT; please see Taneyhill and Schiffmacher (2017) for a thorough review of this topic. Here, we will focus specifically on E-cadherin and N-cadherin’s relevance to both the NC and cancer.…”
Section: Delamination and Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%